PENGARUH LITERASI KEUANGAN SYARIAH, PENDAPATAN DAN RELIGIOSITAS TERHADAP MINAT MEMBUAT PERENCANAAN KEUANGAN ISLAM PADA GENERASI MILENIAL - Dini Hayati Fajrin (2023)
Islamic financial planning is very important to be carried out by the younger generation in the era of the industrial revolution 4.0, where advances in technology and the internet are increasingly sophisticated, making the lifestyle of the millennial generation more consumptive. Islamic financial planning is needed so that financial management becomes clearer and more directed according to Islamic principles, but interest is still low in making Islamic financial planning among the younger generation. The purpose of this study was to analyze the effect of Islamic financial literacy, income, and religiosity on the interest in making Islamic financial planning in the millennial generation. The population of this study is the Jabodetabek millennial generation. Sampling by purposive sampling. A sample of 170 respondents with the criteria of the millennial Muslim generation in Jabodetabek, has an income and has studied Islamic finance. The approach used is quantitative. Questionnaires are used as data collection techniques. Data analysis technique using SEM PLS. Data testing uses the outer and inner models. The results of the R-Square value of 0.862 indicate that Islamic financial literacy, income and religiosity can explain the dependent variable of this study, namely interest is 86.2% and 13.8% is explained by other variables outside this research model. The results of the hypothesis test show that Islamic financial literacy, income and religiosity have a significant effect on interest in making Islamic financial planning.